Cultural Spillovers: Copyright, Conceptions of Authors, and Commercial Practices. Issue 1 (29th November 2017) - Haveman, Heather A.; Kluttz, Daniel N.
Abstract : Economists, sociologists, and legal scholars agree that intellectual‐property law is fundamental to markets because legal control over copying motivates creative production. But in many markets, such as fashion and databases, there is little or no intellectual‐property protection, yet producers still create innovative products and earn profits. Research on such "negative spaces" in intellectual‐property law reveals that social norms can constrain copying and support creative production. This insight guided our analysis of markets for American literature before the Civil War, in both magazines (a negative space, where intellectual‐property law did not apply) and books (a positive space, where intellectual‐property law did apply). We observed similar understandings of authors and similar commercial practices in both spaces because many authors published the same work in both spaces. Based on these observations, we propose that cultural elements that develop in positive spaces may spill over to related negative spaces, inducing changes in buyers' and sellers' behavior in negative spaces. Our historical approach also revealed nuances—shades of gray—beyond the sharp distinction typically drawn between negative and positive spaces. In the 1850s, a few large‐circulation magazine publishers began to claim copyright, but many still allowed reprinting and none litigated to protect copyright.